Comprehensive microsurgical anatomy of the middle cranial fossa: Part I—Osseous and meningeal anatomy - Tayebi Meybodi, Ali; Mignucci-Jiménez, Giancarlo; Lawton, Michael T.; Liu, James K.; Preul, Mark C.; Sun, Hai (Frontiers in Surgery, 2023)
The middle cranial fossa is one of the most complex regions in neurosurgery and otolaryngology—in fact, the practice of skull base surgery originated from the need to treat pathologies in this region. Additionally, the great neurosurgeons of our present and past are remembered for their unique methods of treating diseases localized in the middle fossa. Their interest in the region stems from the fact that the middle fossa contains and acts as a conduit for some of the essential anatomy in the cranial cavity—e.g., the trigeminal nerve and the posterior circulation. The following article reviews the important structural anatomy of the middle fossa, including references and measurements from recent cadaveric-based studies. The review is divided into the anatomy of the bones, dura, vasculature, and nerves—in two parts. Emphasis is paid to their neurosurgical significance and applications in surgery. Part I focuses on the bony and dural anatomy.